2020
DOI: 10.1016/j.ejphar.2020.173329
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin is a potential adjuvant to improve clinical outcomes in individuals with obesity and diabetes with coexistence of Covid-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 77 publications
0
54
0
1
Order By: Relevance
“…Many studies have highlighted the importance of intracellular redox status as a new target for natural medicines, or synthetic drugs aimed at blocking both viral replication and virus-induced inflammation [38]. It has been suggested that, during COVID-19, the early treatment with antioxidants, such as N-acetylcysteine [49,50], melatonin [51,52], polyphenols [53][54][55], K, C, D, and E vitamins supplementation [56].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Many studies have highlighted the importance of intracellular redox status as a new target for natural medicines, or synthetic drugs aimed at blocking both viral replication and virus-induced inflammation [38]. It has been suggested that, during COVID-19, the early treatment with antioxidants, such as N-acetylcysteine [49,50], melatonin [51,52], polyphenols [53][54][55], K, C, D, and E vitamins supplementation [56].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This is also the case with COVID-19, in which many antioxidants such as vitamins A, C, D, melatonin, resveratrol, reduced glutathione, N-acetylcysteine, silymarin, quercetin, artemisinin, curcumin, Boswellia, and hesperidin are currently being evaluated in clinical trials. Likewise, other drugs with antioxidant effects such as statins, colchicine, or amiodarone, have been suggested as part of the arsenal to treat, or at least attenuate, COVID-19 symptoms and sequelae [ 122 , 123 , 124 , 125 ]. Therefore, lessons learned in previous trials using antioxidants in sepsis may serve to hypothesize the therapeutic possibilities of these agents in COVID-19.…”
Section: Antioxidant Therapies In Severe Cases Of Covid-19mentioning
confidence: 99%
“…Under the additional stress of the virus infection, especially, when melatonin synthesis is targeted by virus, the extremely low melatonin may contribute to a collapse of mitochondrial function and decreased tolerance of obese persons to the virus infection. Therefore, the use of melatonin has been suggested to improve the clinical outcome in COVID-19 patients with obesity and diabetes [ 192 ]. In cardiovascular disease and hypertension, patients usually suffer from melatonin deficiency and are prone to heart infarction or sudden death [ 116 , 193 , 194 ].…”
Section: The Outcomes Of Covid-19 Are Potentially Linked To Melatomentioning
confidence: 99%